CONTRIBUTION OF ENGLISH SPEAKERS TO SOUTH AFRICAN HISTORY - Johnson, G.H.T. (Scientia Militaria - South African Journal of Military Studies, 2012)
When I was invited to make a contribution to this column, I asked the Editor to give me some sort of guide line on what he saw as being the nature of the column. The reply he gave was: It is intended to be a forum where one can grind one’s favourite axe about the South African Defence Force; one does not have to tread on anYO’1e’s toes; in order to allow a similar measure of academic freedom as enjoyed by such prestigious periodicals as the United States Naval Institute Proceedings, contributions do not have to be vetted . by one’s boss. Looking at these guide lines I can’t help thinking that whichever course of action I choose ... This leaves me with the difficult task of choosing an appropriate axe that needs grinding. The one that comes to my mind almost immediately is the lack of articles in Militaria on the history of the English speaking folk in South Africa. Before I go any further let me point out to the negativists (to whom any comment will always appear as adverse or destructive criticism) that one can be FOR something without being AGAINST something else.